Association of the Fractalkine Level with Non-modiﬁable and Modiﬁable Factors of Cardiovascular Risk, the Severity of the Atherosclerotic Lesions of the Coronary Vessels - Lopina N. (Львівський клінічний вісник)
The purpose of research is to evaluate the association of fractalkine level with non-modiﬁable and modiﬁable factors of cardiovascular risk, and the severity of the atherosclerotic lesions of the coronary arteries. Materials and Methods. 131 patients with coronary artery disease (CAD) were examined. Depending on the presence of type 2 diabetes mellitus (T2DM), patients with CAD were divided into 2 groups: 1st group (n = 70) – patients with concomitant T2DM, 2nd group (n = 61) – patients with CAD without T2DM. All patients were performed coronary angiography to verify the diagnosis of CAD. Also in all patients were evaluated anthropometric indicators, the levels of fractalkine, indexes of lipid and carbohydrate metabolism. Results. The study found that patients with CAD both with concomitant T2DM and without had increased levels of fractalkine signiﬁ cantly compared with the control group. In patients with hemodynamically signiﬁcant stenosis, diffuse coronary lesions with concomitant T2DM and without had signiﬁcantly higher fractalkine levels. In assessing the relationship fractalkine with non-modiﬁable risk factors there were established the presence of a weak correlation with age, unreliable weak correlation with experience of T2DM, no statistically signiﬁcant average correlation with experience of CAD. In assessing the relationship fractalkine with anthropometric indices there were established the presence of a weak correlation with weight, the volume of the thighs, the ratio of waist size and hip and average positive correlation with a volume of waist, which conﬁ rms the fact that the abdominal obesity increases the synthesis of fractalkine adipocytes. In assessing the relationship fractalkine with lipid metabolism, it was found the presence of a weak correlation with total cholesterol, triglycerides, VLDL, the level of LDL cholesterol. In assessing fractalkine relationships with indicators of carbohydrate metabolism, has been established the presence of a weak correlation with the index of a short-term glycemic control – glucose and secondary with an indicator of a long-term glucose control – HbA1c. The analysis of correlations between the level of fractalkine and severity of CAD has been established the existence of signiﬁcant correlations: strong – between the amount of atherosclerotic plaques of coronary vessels, the middle – between the number of affected vessels, the number of diseased coronary artery segments, weak – the number of lesions of the proximal middle and distal segments, the number of hemodynamically signiﬁcant stenosis of the coronary arteries. Conclusions. Results of the study demonstrate the impact on the level of fractalkine age, duration of CAD, metabolic status and indicators of glycemic control, abdominal obesity. Increasing fractalkine level is associated with more severe atherosclerotic process. The study shows the impact on the development and progression of atherosclerosis, endothelial dysfunction, especially in patients with concomitant T2DM and abdominal obesity.